Implementation of Hots Based (High Order Thinking Skill) Physical Education Learning to Learning for Physical Education Teacher In Masohi Central Maluku - Jonas Solissa; Yellia Tomasoa; Mariana Hukubun; Mesak Hattu (UNIB Press, 2023)
The aims of this research are: 1). To find out the description of implementation, obstacles, and solutions from HOTS-based learning, 2). To find out how teachers implement HOTS in the learning process. The subjects of this study were 21 PJOK teachers in Central Maluku District, Maluku Province at the senior high school level. This research is a type of experimental research using a quantitative descriptive approach to the survey method. Instruments used for data collection namely Questionnaire with a rating scale in a rubric using a Likert scale.Based on the results of the research and data analysis, it shows that: 1) In the implementation of PJOK learning in high schools in Central Maluku district, Maluku Province, there are several obstacles in the application of learning. 2) The implementation of HOTS-based PJOK learning in junior high schools in Central Maluku Regency was in the adequate category with a score of 71.43% or only 15 teachers implemented HOTS-based learning with all the limitations.